2020
DOI: 10.1111/ijsa.12296
|View full text |Cite
|
Sign up to set email alerts
|

Is it enough to be willing to win or do you have to be smart? The relationship between competitive worldviews, cognitive abilities, and applicant faking in personality tests

Abstract: Recent research has highlighted competitive worldviews as a key predictor of faking—the intentional distortion of answers by candidates in the selection context. According to theoretical assumptions, applicants’ abilities, and especially their cognitive abilities, should influence whether faking motivation, triggered by competitive worldviews, can be turned into successful faking behavior. Therefore, we examined the influence of competitive worldviews on faking in personality tests and investigated a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
7
2
Order By: Relevance
“…To the best of our knowledge, no other study has explored this in the past. We acknowledge that the effect sizes were small (although their paths were significant) in most of the relationships when compared to previous studies like those conducted by Roulin and Bourdage (2017) -0.46;Schilling et al (2020) -0.49 for competitive worldviews; and Roulin and Krings (2016) -0.45 for Machiavellianism. Bearing in mind the small effect sizes, generalization of the findings from this study should be done with caution till such time other studies test similar models and report large effect sizes.…”
Section: Summary Of Hypothesescontrasting
confidence: 56%
“…To the best of our knowledge, no other study has explored this in the past. We acknowledge that the effect sizes were small (although their paths were significant) in most of the relationships when compared to previous studies like those conducted by Roulin and Bourdage (2017) -0.46;Schilling et al (2020) -0.49 for competitive worldviews; and Roulin and Krings (2016) -0.45 for Machiavellianism. Bearing in mind the small effect sizes, generalization of the findings from this study should be done with caution till such time other studies test similar models and report large effect sizes.…”
Section: Summary Of Hypothesescontrasting
confidence: 56%
“…In line with this argument, several theoretical models have identified applicants’ cognitive ability as a crucial determinant of the occurrence and magnitude of faking behavior (e.g., Marcus, 2009; Snell et al., 1999; Tett & Simonet, 2011). However, previous empirical results were inconclusive, while a substantial proportion of studies found a corresponding effect (Grubb & McDaniel, 2007; Levashina et al., 2014; Pauls & Crost, 2005), others did not (Furnham et al., 2008; Levashina et al., 2009; Mudgett, 2000; Schilling et al., 2020). Not only are results inconclusive, it is also unclear why there are such inclusive results.…”
Section: Introductionmentioning
confidence: 98%
“…However, some studies have not obtained this result. For example, research by Schilling, Sparfeldt, et al (2020) provides robust evidence of cognitive ability not influencing the degree of faking. Two other studies also found no significant effect of cognitive ability, although these studies provide less compelling evidence.…”
Section: Introductionmentioning
confidence: 99%